Upaya Preventif Penyakit Degeneratif Jantung dan Hipertensi di RSUMM Kota Metro - APRILIANTI, RIZKY; PERTIWI, WINDI; CATUR, YOGI; Mayasari, Fitri; Dhini Yumaniar; FRIEZSHIA, ANNIESHA (Journal of Hospital Administration and Excellent Health Service, 2025)
Introduction: Degenerative diseases such as heart disease and hypertension are major health issues thatare increasingly prevalent in Kota Metro. This study aims to evaluate preventive measures implemented byRSUMM using a qualitative approach with a cross-sectional design. The study population comprisedvisitors to RSUMM’s outpatient clinic, with a sample of 80 individuals selected from a total population of120. Data collection techniques included observation and in-depth interviews. The results showed that 85%of respondents had good knowledge about degenerative diseases, 60% demonstrated good behavior, 78%had a healthy lifestyle, 80% maintained a good diet, and only 49% routinely underwent medical check-ups.These findings indicate the need for enhanced preventive education and improved medical check-upfacilities to reduce the risk of degenerative diseases in the communityKeyword: Degenerative diseases, heart disease, hypertension, preventive measures, RSUMM Kota Metro.